The Politics of Income Inequality in the OECD: The Role of Second Order Effects - Pablo Beramendi Alvarez (Luxembourg Income Study (LIS), 2001)
Why, contrary to Meltzer and Richard's prediction (1981), do nations with low levels of wage inequality have large welfare states? Why in turn, consistently with MR (1981), do many of these same nations have large levels of market income inequality? This paper points to the role of second order effects of redistributive policies as the key to solve the theoretical puzzle posed by these to empirical phenomena. The first half of the paper introduces the notion of several orders of incidence of redistribution as well as a theoretical discussion of the two major mechanisms through which second order effects take place: the impact of redistribution on labor supply and the interaction between these second order effects and different institutional aspects of advanced industrial societies, most prominently the collective bargaining institutions. Thereafter the argument is tested by analyzing the determinants of wage and market income inequality in 15 OECD nations between 1980 and 1995.
Keywords: 330; Einkommensverteilung; Einkommensumverteilung; OECD-Staaten